2020
DOI: 10.3390/antibiotics9060284
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Susceptibility to Selected Antibiotics in Klebsiella pneumoniae, Escherichia coli, Enterococcus faecalis and Enterococcus faecium Causing Urinary Tract Infections in Kidney Transplant Recipients over 8 Years: Single-Center Study

Abstract: Background: Urinary tract infections (UTIs) are the most common bacterial infections among kidney transplant (KTX) recipients. The purpose of this study was to analyze antimicrobial resistance (AMR) in four most common pathogens responsible for UTIs in KTX recipients and determine risk factors (RF) for resistance in the same group. Methods: Analyzed antibiograms were based on urine samples positive for bacterial growth of 105 colony-forming units (CFU)/mL obtained from hospitalized adult KTX recipients present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
2
8
2
Order By: Relevance
“…Overall, we observed high prevalence of virulence factors common in UTIs in different geographic areas, i.e., gelatinase ( gelE ) and adhesins ( efaA , esp ), that facilitate colonization of urothelial cells, biofilm formation and exchange of genetic material, tissue damage, and resistance to some bioactive peptides [ 28 , 29 , 30 , 31 ]. Antibiotic sensitivity was in a similar range as other studies conducted on E. faecalis isolated from UTIs, with the highest sensitivity to β-lactams, glycopeptides, linezolid, and fosfomycin and intermediate susceptibility to aminoglycosides or streptomycin [ 32 , 33 , 34 ]. Remarkably, there was not a correlation between virulence factors and antibiotic resistance among the clinical isolates ( Tables S1 and S2 ).…”
Section: Discussionsupporting
confidence: 68%
“…Overall, we observed high prevalence of virulence factors common in UTIs in different geographic areas, i.e., gelatinase ( gelE ) and adhesins ( efaA , esp ), that facilitate colonization of urothelial cells, biofilm formation and exchange of genetic material, tissue damage, and resistance to some bioactive peptides [ 28 , 29 , 30 , 31 ]. Antibiotic sensitivity was in a similar range as other studies conducted on E. faecalis isolated from UTIs, with the highest sensitivity to β-lactams, glycopeptides, linezolid, and fosfomycin and intermediate susceptibility to aminoglycosides or streptomycin [ 32 , 33 , 34 ]. Remarkably, there was not a correlation between virulence factors and antibiotic resistance among the clinical isolates ( Tables S1 and S2 ).…”
Section: Discussionsupporting
confidence: 68%
“…The results also showed an increase in the number of Gram-positive uropathogens especially Enterococcus faecalis and Enterococcus facium. Several previous studies showed the emergence of non-Enterobacteriaceae, i.e., Enterococcus faecalis and Enterococcus facium as primary causative agents for urinary tract infections (Parameswarappa et al 2013;Shrestha et al 2019;Rostkowska et al 2020). Therefore, Enterococcus faecalis and Enterococcus facium are projected in contributing to the rapid increase of multidrug resistance due to their intrinsic resistance plus genetic diversity, including resistance to the well-known synthetic drugs to prevent urinary tract infections such as nitrofurantoin (Zhang et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Statistical data on uropathogens causing UTIs in kidney transplant recipients presented by four groups of Polish authors showed different results depending on the transplant centre in Poland ( Gołębiewska et al., 2011 ; Adamska et al., 2015 ; Gozdowska et al., 2016 ; Rostkowska et al., 2020 ). Furthermore, the results from the same centre but from different study periods also varied.…”
Section: Epidemiology Of K Pneumoniae Uti In Kidne...mentioning
confidence: 99%